DESAIN MODEL PEMBELAJARAN MENULIS NASKAH DRAMA BERDASARKAN ANALISIS KEMAMPUAN MENULIS NASKAH DRAMA MAHASISWA FKIP UNJA - Irma Suryani (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
The background of this research is it is very important for the university students to write about the script of drama, but actually the students’ ability in writing the script of drama is still limited. One of the source of this problembs is the teaching model of writing script of drama is not appropriate. So that it is important to develop the model of drama script writing. This research will use descriptive qualitative method. The data collection of this research are observation and test. The technique analysis data is content analysis and library research. To increase the students’ affective, pshycomotori, and cognitive competence in writing drama script, three fases activities is designed as individual-group-individual.Keywords: model design, drama script writing, content analysis